EVALUATION OF ULCEROPROTECTIVE ACTIVITY OF MUSA SAPIENTUM VAR. PARADISIACA METHANOLIC FRUIT EXTRACT AGAINST ASPIRIN INDUCED GASTRIC ULCERS IN ALBINO RATS - Barua, Nilotpal; Das, Swarnamoni (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: The objective of the study was to evaluate the ulceroprotective activity of Musa sapientum var. paradisiaca methanolic fruit extract (MSE) against aspirin induced gastric ulcers in albino rats. Methods: Fresh plantain bananas were sliced and air dried at room temperature. The dried slices were ground to a fine powder. The extract was prepared by percolating dried powder with methanol. Twenty four healthy albino rats of 100-200 gms were taken for the study. The animals were divided into four groups of six animals each. Group I or control (3percent gum acacia 5 ml/kg orally for 7 days). Group II or experimental control (aspirin 400 mg/kg orally single dose on the 7th day). Group III or MSE group (MSE 100 mg/kg orally for 7 days and aspirin 400 mg/kg orally single dose on the 7th day). Group IV or standard (ranitidine 150 mg/kg orally for 7 days and aspirin 400 mg/kg orally single dose on the 7th day). On 8th day the stomachs of the sacrificed rats were removed and (1) ulcer index (2) total acidity (3) free acidity (4) gastric mucous secretion were studied. Results: The ulcer index, free and total acidity in group III and IV showed significant decrease in comparison to group II (p <0.01) whereas there was increase in gastric mucus secretion (p <0.01). Conclusion: The study showed significant ulceroprotective activity of Musa sapientum var. paradisiaca methanolic fruit extract (MSE) against aspirin induced gastric ulcers in albino rats. KEYWORDS Aspirin, free acidity, gastric mucous, Musa sapientum var. paradisiaca, percolation, peptic ulcer, ranitidine, total acidity, ulcer index Abbreviation: MSE – Musa sapientum var. paradisiaca extract